Modeling the dark personality traits according to childhood trauma: the mediating role of guilt sense and anxiety - Zainab Jahangir Kalestan; Afshin Salahian; Bita Nasrollahi (Shahid Beheshti University of Medical Sciences, 2023)
Background: The dark aspects of personality, including the three traits of narcissism, antisocialism, and Machiavellianism were in the spotlight in the last decade. This study was aimed to modeling the prediction of dark personality traits according to childhood trauma with the mediating role of guilt sense and anxiety Methods: This research was a correlational study and based on the structural equation modeling method. In the study, all students of the University in the academic year 2020-2021.were included, and 382 people were selected as convenience sampling. Here, the dark personality traits questionnaire, anxiety scale, guilt sense scale and childhood trauma questionnaire were used. Data analysis was performed using AMOS 18 software, correlation coefficient, factor analysis, and fit indices. Results: The results indicated that the path of childhood trauma to dark personality traits is not significant. After examining the fit indices, guilt sense did not soundly play a mediating role in the correlation between childhood traumas and dark personality traits (P=0.39), while childhood traumas through anxiety had a significant indirect relationship with dark personality traits (P<0.05). Conclusion: To reduce the effects of dark personality traits, attention should be paid to childhood traumas. Childhood traumas can increase dark personality traits in a person through the mediation of anxiety. .